2007
DOI: 10.4081/ijas.2007.187
|View full text |Cite
|
Sign up to set email alerts
|

Entrance order and side preference of dairy cows in the milking parlour

Abstract: Sixty-seven multiparous (group M) and 79 primiparous (group P) Friesian cows were used to assess the consistency of the order of entry and the preference for a determinate side into the milking parlour. The Kendall's coefficient of concordance showed a constancy of the entrance order into milking parlour for both primiparous and multiparous subjects (0.36, P<0.001). In primiparous cows milk yield was significantly correlated to entrance order (r s =0.22, n=79, P<0.05) and tended to be correlated to SCC (r s =0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 18 publications
5
27
0
2
Order By: Relevance
“…The day to day milking order appeared to be very weakly but significantly consistent during the observation period, indicating that cows tended to follow a repeatable order when walking into the milking parlour. This consistency of milking order has also been found in other studies in dairy cattle (Grasso et al, 2007), buffalo cows (Polikarpus et al, 2014) and sheep (Villagrá et al, 2007). Polikarpus et al (2015) found that milking order in dairy cows was consistent within and across days, but seemed to be more variable within milking sessions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The day to day milking order appeared to be very weakly but significantly consistent during the observation period, indicating that cows tended to follow a repeatable order when walking into the milking parlour. This consistency of milking order has also been found in other studies in dairy cattle (Grasso et al, 2007), buffalo cows (Polikarpus et al, 2014) and sheep (Villagrá et al, 2007). Polikarpus et al (2015) found that milking order in dairy cows was consistent within and across days, but seemed to be more variable within milking sessions.…”
Section: Discussionsupporting
confidence: 83%
“…Polikarpus et al (2015) found that milking order in dairy cows was consistent within and across days, but seemed to be more variable within milking sessions. The milking parlour used in this study had a right and a left side and, in addition to consistency in milking order, cows have shown a side preference, as described by Grasso et al (2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…No relation between milk yield and entry order into milking parlour was observed in Manchega sheep (Villagra et al 2007). However, higher milk yield in animals entering the parlour early was observed in goats and cows (Margetinova Grasso et al 2007). Animals in FG had higher peak flow rate and needed shorter time to start milk flow (latency time) than LG ewes (1.04 vs 0.77 l/min and 14 vs 20 s, respectively (P < 0.01)).…”
Section: Resultsmentioning
confidence: 99%
“…Relação inversa entre produção de leite e contagem de células somáticas foi observada no presente estudo após o transporte. Alguns autores também observaram a mesma relação em outras situações estressantes (Hinckley, 1983;Zeng e Escobar, 1995;Grasso et al, 2007 …”
Section: Resultsunclassified